2013
DOI: 10.1111/ene.12262
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile and thyroid hormone concentrations in children with epilepsy treated with oxcarbazepine monotherapy: a prospective long‐term study

Abstract: OXC monotherapy may cause significant and persistent alterations in lipid and thyroid profiles in children with epilepsy. The increase in LDL-C and TC levels may be associated with liver enzymes induction and thyroid dysfunction. Further long-term prospective studies are required to confirm these findings and to determine their clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…These results agreed with those of Yılmaz et al 11 On studying the effect of oxcarbazepine on thyroid hormone levels in epileptic patients, we found significantly lower FT4 levels in patients while no significant difference was found in T3, T4, and TSH levels between patients and controls. These results agree with those of Yılmaz et al 11 and Garoufi et al 20 Oxcarbazepine, a 10-keto analogue of carbamazepine, was developed as an attempt to reduce the side effects that had been observed with administration of carbamazepine. 11 Despite its close structural resemblance, oxcarbazepine does not induce enzyme activity to a similar extent as does carbamazepine.…”
Section: Discussionsupporting
confidence: 89%
“…These results agreed with those of Yılmaz et al 11 On studying the effect of oxcarbazepine on thyroid hormone levels in epileptic patients, we found significantly lower FT4 levels in patients while no significant difference was found in T3, T4, and TSH levels between patients and controls. These results agree with those of Yılmaz et al 11 and Garoufi et al 20 Oxcarbazepine, a 10-keto analogue of carbamazepine, was developed as an attempt to reduce the side effects that had been observed with administration of carbamazepine. 11 Despite its close structural resemblance, oxcarbazepine does not induce enzyme activity to a similar extent as does carbamazepine.…”
Section: Discussionsupporting
confidence: 89%
“…A recent prospective study on 23 children receiving OXC [78] showed that FT4, but not FT3, was significantly reduced after 8 and 18 months treatment, while TSH was significantly increased.…”
Section: Thyroid Functionmentioning
confidence: 97%
“…However, no direct effects of ESL on lipid metabolism profile were concluded in those studies. Prior studies have demonstrated adverse effects of older dibenzazepines and other metabolic inducers on lipid metabolism profile (Chuang et al, 2012;Nikolaos et al, 2004), while authors have suggested a milder but still deleterious effect of OXC (Franzoni et al, 2006;Garoufi et al, 2014;Papacostas, 2000;Yiş and Dogan, 2012), and little is known regarding the effects of ESL. In patients with epilepsy presence of dyslipidemia related to chronic use of AEDs represents a chronic vascular risk factor (Cockerell et al, 1994), with the consequent increased mortality due in part to the increased vascular risk (Chuang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%